2007
DOI: 10.1007/s12149-007-0027-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of brain tumor recurrence by 99mTc-tetrofosmin SPECT: a prospective pilot study

Abstract: Metabolic brain imaging by (99m)Tc-TF could offer useful information in the workup of treated brain tumors, where radiomorphologic findings between recurrence and radionecrosis are inconclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 22 publications
1
29
0
1
Order By: Relevance
“…In both tumor types we verified a strong positive linear correlation between tracer uptake and tumor proliferative potential and aggressiveness [4][5][6]. Furthermore, we reported that 99m Tc-TF SPECT could hold a role in differentiating tumor recurrence from radiation necrosis and neoplastic from non-neoplastic intracerebral hemorrhage [7,8]. We therefore propose 99m Tc-TF SPECT as a cost-effective functional imaging modality that offers a noninvasive method for quantitating cellular proliferation in gliomas thus assisting therapeutic decision-making and prognosis estimation.…”
supporting
confidence: 69%
“…In both tumor types we verified a strong positive linear correlation between tracer uptake and tumor proliferative potential and aggressiveness [4][5][6]. Furthermore, we reported that 99m Tc-TF SPECT could hold a role in differentiating tumor recurrence from radiation necrosis and neoplastic from non-neoplastic intracerebral hemorrhage [7,8]. We therefore propose 99m Tc-TF SPECT as a cost-effective functional imaging modality that offers a noninvasive method for quantitating cellular proliferation in gliomas thus assisting therapeutic decision-making and prognosis estimation.…”
supporting
confidence: 69%
“…99m Tc-sestamibi has been extensively used and proved useful for metabolic characterization (16). 99m Tc-tetrofosmin is a lipophilic diphosphine that has also proven suitable for brain tumor imaging (10,11,(17)(18)(19). Its uptake in the healthy brain is physiologically seen in the choroid plexus and the pituitary gland but not in the normal brain parenchyma, because it does not cross the intact blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…We have recently shown in vivo that, in contrast to 99m Tc-sestamibi, 99m Tc-tetrofosmin is not influenced by the multidrug-resistance phenotype of gliomas and may thus be superior for brain tumor imaging (18). Furthermore, 99m Tc-tetrofosmin can be a suitable radiotracer for the differentiation of glioma recurrence from radiation necrosis, neoplastic from nonneoplastic intracerebral hemorrhage, and benign from malignant brain space-occupying lesions and for the assessment of the proliferation potential of gliomas and meningiomas (19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…Morphological depiction of the brain by classic MRI and CT can merely recognize edema and BBB disruption, so it is usually inconclusive and faces inherent limitations in discriminating viable tumor from post-irradiation change (Byrne, 1994). Depiction of recurrent tumor was the first imaging challenge against which we evaluated 99m Tc-TF brain SPECT accuracy a few years back (Alexiou et al, 2007). A prospective ongoing study enrolled 24 patients that had been previously treated surgically for brain tumor followed by external beam radiotherapy, while some had also received adjuvant chemotherapy.…”
Section: Discriminating Recurrent Disease From Radiation Necrosis In mentioning
confidence: 99%